Bowel injury: a rare but dreaded complication of unsafe abortion - Ramola, Monika; Chaudhari, Priyanka; Singh, Parul; Ramola, Mahesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Unsafe abortions represent a preventable yet major cause of maternal mortality and morbidity in India. Intestinal perforation is a rare dreaded complication of unsafe abortion. It is commonly seen in countries in which abortions are performed by people without proper training and proper instruments. Bowel perforation occurs when the posterior vaginal wall or the uterine wall is perforated. The ileum and the sigmoid colon are the most commonly injured portion of the bowel. Here, we report a case of ileal perforation following induced unsafe abortion which was managed successfully.